Modelagem de Pára-Raios de ZnO para o cálculo de tensão induzida por descarga atmosférica em redes de distribuição - Leandro Chagas Alves (2010)
The competitiveness of the energy market and the action of regulatory agencies require, nowadays, from the electric utility an extremely reliable power supply that should comply with several power quality ratings (short-term voltage variation, unbalanced voltage, harmonics, steady state voltage, etc.). Thus an eective surge protection system is fundamental to any utility in order to provide a good power quality. As already shown in many studies, the overvoltage induced by lightning is the main cause of problems in overhead distribution networks. In modern systems, the additional use of zinc oxide (ZnO) lightning arrester has been a good solution to limit these disturbances, avoiding powerinterruptions in distribution and transmission lines. This work presents a program to calculate induced voltage by indirect lightning strokes on overhead distribution lines equipped with ZnO arresters. The routine was implemented in a transients program based on the Rusck's theory (Rusck-EMTP Method). The implemented routine allows the estimation of induced voltage in large networks. To validate the results of the implemented methodology, tests were performed to calculatethe induced voltage in a three-phase distribution line, varying the location of indirect lighting stroke, the quantity and the position of the arresters.The results showed that the developed software provides a good estimate of induced voltages in complex distribution systems equipped with metal oxide arresters. The implemented methodology can, therefore, be considered an enlargement of the potentiality of EMTP-like programs.